A Scale for Measuring Healthcare Service Quality Incorporating Patient-Centred Care and Using a Psychometric Analytics Framework (2022)
ABSTRACT: Recent developments in healthcare contexts increasingly emphasize patient-centred approaches to service quality measures; however, few studies consider this dimension explicitly. The present study develops and psychometrically validates a scale of healthcare service quality explicitly incorporating a patient-centred care dimension from a communicational perspective. The paper also enriches the traditional content of service quality by including equity items and presents the underlying structure of service quality in an emerging country. The final sample consisted of 869 healthcare users (complete cases in the service quality items derived from 917 surveys received) from Colombia. We used a psychometric analytics framework comprising seven processes incorporating exploratory factor analysis, structural equation modelling, and machine learning methods to examine construct plausibility, reliability, construct validity, equity, and criterion/predictive validity (e.g. explaining/predicting subjective well-being and behavioural intentions). The final scale consists of 17 items and satisfies all psychometric properties. Its validation allows for the discovery and psychometrical confirmation of two essential dimensions: patient-centred communication (eight items) and process quality (nine items). Both dimensions reveal users’ relevant needs and complement previous studies that have focused on process aspects of healthcare service quality. We illustrate three practical uses of the scale: the possibility for diagnoses; hypothesis contrast based on confidence intervals; and estimation of the capacity of the service to satisfy specifications.